Prevalence and Changing Virulence Factors and Biofilm Formation among Non-Albicans Candida Species in Suspected Vulvovaginitis Infections - Rahul Gopichand Walide1*; Ahire Karuna R2; Ravidas Vasave1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Vulvovaginal candidiasis (VVC), a common gynecological condition predominantly attributed to Candida albicans, frequently affects pregnant women. Non-albicans Candida species (NACs) are increasingly recognized as important etiological agents, potentially contributing to adverse pregnancy outcomes such as preterm birth and miscarriage. This study aimed to determine the prevalence of NACs and characterize their virulence factor profiles, including biofilm formation, in women with suspected vulvovaginitis, with the goal of informing and optimizing clinical management strategies for this condition. Methods: Cervicovaginal swabs were prospectively collected from pregnant women presenting with clinical signs and symptoms suggestive of vulvovaginitis. Identification of Candida species was performed using standard mycological techniques, encompassing microscopic examination, germ tube testing, and carbohydrate assimilation tests. The assessment of virulence factor production included biofilm formation, and the enzymatic activities of hemolysin, phospholipase, lipase, and protease (evaluated via agar diffusion assays). Statistical analyses were conducted using SPSS software (version 25.0). Results: Among the 370 cervicovaginal swabs collected from women presenting with suspected vulvovaginitis, Candida species were identified in 123 swabs (33.24%). C. albicans constituted 53.66% of the isolates, while NACs accounted for the remaining 46.34%. Within the NACs isolates, Candida tropicalis (49.12%) and Candida glabrata (28.07%) were the predominant species. Diabetes mellitus was the most common risk factor identified in women with Candida infection. Hemolysin production was the most frequently detected virulence factor among the NACs isolates, observed in 40.9% of these isolates. Conclusion: This study demonstrates the significant prevalence of NACs in vulvovaginal candidiasis cases, concurrent with the notable presence of diverse virulence factors. Our findings underscore the importance of routine mycological investigations for accurate species identification and suggest that virulence factor profiling may be critical for informing effective management strategies for VVC, particularly given the observed prevalence and potential pathogenic implications of the diverse array of virulence factors among NACs.